Neural Mechanisms of Social and Nonsocial Reward Prediction Errors in Adolescents with Autism Spectrum Disorder. Issue 5 (11th February 2020) - Kinard, Jessica Lynn; Mosner, Maya Gelman; Greene, Rachel Kirsten; Addicott, Merideth; Bizzell, Joshua; Petty, Chris; Cernasov, Paul; Walsh, Erin; Eisenlohr‐Moul, Tory; Carter, Ronald McKell; McLamb, Marcy; Hopper, Alissa; et al.
Abstract : Autism spectrum disorder (ASD) is characterized by impaired predictive abilities; however, the neural mechanisms subsuming reward prediction errors in ASD are poorly understood. In the current study, we investigated neural responses during social and nonsocial reward prediction errors in 22 adolescents with ASD (ages 12–17) and 20 typically developing control adolescents (ages 12–18). Participants performed a reward prediction error task using both social (i.e., faces) and nonsocial (i.e., objects) rewards during a functional magnetic resonance imaging scan. Reward prediction errors were defined in two ways: (a) the signed prediction error, the difference between the experienced and expected reward; and (b) the thresholded unsigned prediction error, the difference between expected and unexpected outcomes regardless of magnitude. During social reward prediction errors, the ASD group demonstrated the following differences relative to the TD group: (a) signed prediction error: decreased activation in the right precentral gyrus and increased activation in the right frontal pole; and (b) thresholded unsigned prediction error: increased activation in the right anterior cingulate gyrus and bilateral precentral gyrus. Groups did not differ in brain activation during nonsocial reward prediction errors. Within the ASD group, exploratory analyses revealed that reaction times and social‐communication impairments were related to precentral gyrus activation during social prediction errors. These findings elucidate the neural mechanisms of social reward prediction errors in ASD and suggest that ASD is characterized by greater neural atypicalities during social, relative to nonsocial, reward prediction errors in ASD. Autism Res 2020, 13: 715–728 . © 2020 International Society for Autism Research, Wiley Periodicals, Inc. Lay Summary: We used brain imaging to evaluate differences in brain activation in adolescents with autism while they performed tasks that involved learning about social and nonsocial information. We found no differences in brain responses during the nonsocial condition, but differences during the social condition of the learning task. This study provides evidence that autism may involve different patterns of brain activation when learning about social information.